Pengaruh Model Pembelajaran Learning Cycle 5E Berbasis STEM terhadap Literasi Sains dan Hasil Belajar Mahasiswa Pendidikan Guru Sekolah Dasar - Rangga Gustiawan Nazara; Fery Muhamad Firdaus; Octavian Muning Sayekti; Panji Hidayat; Waode Sitti Fatimah; Zeni Dwi Adiningsih (Postgraduate, University of Mataram, 2026)
This study examines the effect of the STEM-based 5E Learning Cycle model on science literacy and learning outcomes of preservice elementary teachers. A quasi-experimental one-group pretest–posttest design was employed involving 29 first-semester students in an Elementary Teacher Education program. The intervention was implemented through STEM-integrated learning activities using hydraulic media across the five phases of the 5E learning cycle. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon signed-rank test, normalized gain (N-gain), and effect size analysis. The results showed a significant improvement in students’ science literacy, with mean scores increasing from 63.45 to 91.72 (p < 0.001). The average N-gain value of 0.7817 indicated a high level of learning improvement, while the effect size analysis revealed a very large effect (Cohen’s d = 2.619). Qualitative findings supported the quantitative results, indicating that hands-on inquiry, structured exploration, and contextual STEM tasks enhanced students’ conceptual understanding and scientific reasoning. In conclusion, the STEM-based 5E Learning Cycle model is effective in improving science literacy and learning outcomes among preservice elementary teachers and holds strong potential for broader application in teacher education.